Joint flight bouts but short-term association in migrating Eurasian Curlews Numenius arquata. Issue 1 (2nd January 2021) - Jiguet, Frédéric; Bocher, Pierrick; Kruckenberg, Helmut; Kämpfer, Steffen; Debenest, Etienne; Lorrillière, Romain; Rousseau, Pierre; Szajda, Maciej; Düttmann, Heinz
ABSTRACT : Capsule: Migration associations by Eurasian Curlews Numenius arquata are temporary and last for single flight bouts between stopover sites. Aims: Migrant shorebirds are known to initiate migration communally, with groups of birds departing simultaneously from wintering or post-breeding fuelling sites, though the duration of such migratory associations is not known. Methods: Wintering and breeding adult Eurasian Curlews, and some hand-reared juveniles, were equipped with GPS tags to record their migration. Results: We describe four cases of joint migration by tagged Eurasian Curlews which provided the opportunity to study the duration of migration associations. Conclusions: Migration associations lasted for one flight bout only, with separate departures from the subsequent stopover site. This implies that associations might involve individuals that are ready to leave at the same time but not those sharing a final destination. Our observations suggest that migratory groups are temporary associations, reminiscent of the dynamics of a fission-fusion society.